Analisis Efektivitas Program Perlindungan Anak Terpadu Berbasis Masyarakat (PATBM) di Desa Tambak Kalisogo Kabupaten Sidoarjo - Novi Andriani Firdaus; Lailul Mursyidah (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2026)
The Community-Based Integrated Child Protection Program (PATBM) in Tambak Kalisogo Village is a collaborative effort between the government and the community to prevent and address violence against children at the village level. This study aims to analyze the effectiveness of the PATBM program based on Sutrisno's theory of effectiveness, which includes program understanding, targeting accuracy, timeliness, goal achievement, and tangible change. The study used a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation studies. The results showed that implementers and the community had a good understanding of the program's objectives and mechanisms, the program was able to reach vulnerable groups and respond to reports through a community-based approach, and case handling was carried out relatively quickly. Program implementers also contributed to a decrease in the number of cases of violence and increased community courage to report. In addition, there was a growing collective awareness and changes in community social attitudes towards child protection issues. These findings indicate that program effectiveness is not only reflected in the number of achievements, but also in social changes and community participation, so that continuous support is needed to strengthen the capacity of cadres and the child protection system at the village level.